The Strategic Role of The Pasangkayu District Government in Handling Stunting Symptoms - Tamar Hasriati Embong Bulan; Hamka Naping; Safriadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Tadulako, 2023)
Stunting is a condition of malnutrition in toddlers characterized by delayed growth and height not in accordance with age and can be influenced by several factors such as nutrition, digestive infections, low birth weight, and environmental health. This study aims to determine the state of stunting in Pasangkayu Regency, Polewali Village, which has a remote indigenous community, the Bunggu tribe. This research also wants to know the national strategic plan for stunting reduction. The method used is descriptive research with a qualitative approach. The descriptive-qualitative method is a research method used to examine the condition of natural objects. The results showed that remote indigenous communities are inseparable from the problems of remoteness and poverty, which are very complex problems. The reality of remote indigenous peoples who are still very difficult to get access to, resulting in the interaction of community behavior being indifferent in paying attention to life problems, especially from the health aspect, one of which is the problem of stunting, while the national strategic plan in implementing the acceleration of national stunting reduction refers as mandated by Presidential Decree 72 of 2021.